The Utilization of sexual and reproductive health services among students: Insight from a Ghanaian University.: Reproductive health - Agyei, Frank Bediako; Suglo, Joseph; Ninnoni, Jerry PK (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
Background: Most Tertiary students are sexually active and are predisposed to sexually transmitted infections and other reproductive health issues. To help protect students from the consequences of unsafe sex, reproductive health services are essential and to be made accessible on campuses and other health facilities.Objective: To determine the level of utilization of sexual and reproductive health services among students in Ghana and any perceived barriers that militated against students’ utilization of these services.Study Design: This was a descriptive cross-sectional study that recruited students from the Presbyterian University College Ghana. Statistical Package for Social Sciences version 21 was used to analyse responses of participants.Results: The study revealed that majority of the respondents have heard about sexual and reproductive health services and knew where they could access these services. However, less than half (29.7%) of the respondents have ever utilized reproductive health services such as family planning services, voluntary counselling for Human Immune Virus and reproductive health counselling. Unfriendly attitude of staff, high cost of services, lack of privacy and confidentiality were identified as major barriers to the uptake of reproductive health services.Conclusion: The uptake of sexual and reproductive health services among students is low due to challenges that related to service providers, community and the healthcare delivery system. It is important that further studies investigating the expectations of students is done in order to introduce student friendly services that will enhance utilization.